Project SIREN A study on effective information retrieval and extraction methods on Philippine news websites for building an automated trauma inventory system - Badaguas, Hannah Maria D.M.; Sze, Jennylyn C.; Tabugadir, Emily Marie A. (2009)
Trauma (or injury from crime or accidents) is the fourth leading cause of death in the Philippines. In the United States, each state has several trauma centres whose main responsibility is to build and maintain a national trauma registry. The registry aids in effective urban planning, law enforcement and injury prevention initiatives. As the Philippines currently has no such trauma centers, it is this project's goal to automate the creation and maintenance of such a registry. Using information retrieval techniques, the system regularly scours local news websites to retrieve injury-related articles. An information extraction system that works effectively on documents is used to extract relevant information, such as the number of victims, the ages and genders of the victims, time, date, place and mechanism of injury. The data gathered is then stored in a database and is presented by means of a graphical user interface that allows users to filter and retrieve data of interest through queries. Statistical reports are provided to aid in effective analysis. After a series of test, our system proved to be effective in retrieving injury-related articles as reflected in its high level of precision and recall. The extraction of relevant information is sufficient and fairly accurate.
Thesis (B.S. Computer Science) -- University of the Philippines, Diliman
Keywords: Natural language processing (Computer science); Data mining; Information storage and retrieval systems; Project SIREN (Project).; Automated trauma inventory system